2021
DOI: 10.1242/jcs.254029
|View full text |Cite
|
Sign up to set email alerts
|

Tensins – emerging insights into their domain functions, biological roles and disease relevance

Abstract: Tensins are a family of focal adhesion proteins consisting of four members in mammals (TNS1, TNS2, TNS3 and TNS4). Their multiple domains and activities contribute to the molecular linkage between the extracellular matrix and cytoskeletal networks, as well as mediating signal transduction pathways, leading to a variety of physiological processes, including cell proliferation, attachment, migration and mechanical sensing in a cell. Tensins are required for maintaining normal tissue structures and functions, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(71 citation statements)
references
References 128 publications
0
71
0
Order By: Relevance
“…The EGFRAP SH2 domain most closely resembles those of the Tensins (FlyBase). Tensins are a family of focal adhesion proteins, composed of four members (Tensin 1–4, TNS1-4), which link the cell membrane to the actin cytoskeleton and are lost in most cancer cell lines [ 66 , 67 ]. EGFRAP and PVRAP have been proposed to be orthologs of human TNS2 and TNS4 (FlyBase), proteins that in knockdown conditions increase tumorigenicity in several cancer lines [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…The EGFRAP SH2 domain most closely resembles those of the Tensins (FlyBase). Tensins are a family of focal adhesion proteins, composed of four members (Tensin 1–4, TNS1-4), which link the cell membrane to the actin cytoskeleton and are lost in most cancer cell lines [ 66 , 67 ]. EGFRAP and PVRAP have been proposed to be orthologs of human TNS2 and TNS4 (FlyBase), proteins that in knockdown conditions increase tumorigenicity in several cancer lines [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the genes showing alteration in paediatric PTCL, TNS1 and ZFHX3 were the first and second targets with similar frequencies respectively, LRP2 was third, and NCOA2 and TET2 belonged to the fourth most frequent group. TNS1 encodes a cytoplasmic phosphoprotein that plays a role in signal transduction between the extracellular matrix and cytoskeleton by binding to actin filaments, leading to a variety of physiological processes, including cell proliferation, 26 and its functional role was both suggested as a tumour suppressor and an oncogene 27 in several types of malignancy, including acute myeloid leukaemia (AML) cells.…”
Section: Discussionmentioning
confidence: 99%
“…3b, c). This was surprising, since the N-terminal PTEN-like region and C-terminal SH2-PTB regions had previously been thought to target tensins to FA (Liao and Lo 2021). We therefore prepared constructs with the tensin3-IDR fused to cBAK or GFP and found that they associated with both talin and vinculin in mitochondrial targeting experiments (Fig.…”
Section: Identification Of Tensin Binding Partnersmentioning
confidence: 99%
“…The middle regions are largely unstructured with little amino acid sequence homology between family members. b, Schematic showing various reported interaction partners (reviewed in (Liao and Lo 2021)) of the tensin family, including: cytoplasmic domains of beta integrin subunits (β1, β3, β5, β7) with the PTB domain that reportedly supports integrin activation (Calderwood et al 2003;Katz et al 2007;McCleverty, Lin, and Liddington 2007); the SH2 domain with p130CAS (Zhao et al 2016); actin to the N-terminus (Lo et al 1994); the Rho GAPs DLC1-3 to both the N-and C-termini (Shih et al 2015;Cao et al 2012;Liao et al 2007;Kawai et al 2009;Qian et al 2007); growth factor receptors (EGFR (Cui, Liao, and Lo 2004;Katz et al 2007), cMET (Muharram et al 2014)) and additional FA proteins (e.g. FAK and p130Cas (Qian et al 2007;Hall et al 2010;Cui, Liao, and Lo 2004), Hic5 (Goreczny, Forsythe, and Turner 2018), ILK (Qian et al 2007)) to the C-terminus.…”
Section: Graphs and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation